Architectural photogrammetry for conservation and restoration of historical building : an experience with MPS-2 system - Ahmad, Anuar (Fakulti Ukur dan Harta Tanah, 2004)
Line drawing is an important product of architectural photogrammetry. It is required for the conservation and restoration works. Normally in architectural photogrammetry the line drawings are produced for heritage purposes such as old and historical buildings. There are a few method in producing line drawings. This paper will discuss one of the methods used in a research for producing line drawing by using the Adam Technology MPS-2 System.